New insights into antiangiogenic therapy resistance in cancer: Mechanisms and therapeutic aspects. (September 2022) - Huang, Maohua; Lin, Yuning; Wang, Chenran; Deng, Lijuan; Chen, Minfeng; Assaraf, Yehuda G.; Chen, Zhe-Sheng; Ye, Wencai; Zhang, Dongmei
Abstract: Angiogenesis is a hallmark of cancer and is required for tumor growth and progression. Antiangiogenic therapy has been revolutionarily developing and was approved for the treatment of various types of cancer for nearly two decades, among which bevacizumab and sorafenib continue to be the two most frequently used antiangiogenic drugs. Although antiangiogenic therapy has brought substantial survival benefits to many cancer patients, resistance to antiangiogenic drugs frequently occurs during clinical treatment, leading to poor outcomes and treatment failure. Cumulative evidence has demonstrated that the intricate interplay among tumor cells, bone marrow-derived cells, and local stromal cells critically allows for tumor escape from antiangiogenic therapy. Currently, drug resistance has become the main challenge that hinders the therapeutic efficacies of antiangiogenic therapy. In this review, we describe and summarize the cellular and molecular mechanisms conferring tumor drug resistance to antiangiogenic therapy, which was predominantly associated with redundancy in angiogenic signaling molecules (e.g., VEGFs, GM-CSF, G-CSF, and IL17), alterations in biological processes of tumor cells (e.g., tumor invasiveness and metastasis, stemness, autophagy, metabolic reprogramming, vessel co-option, and vasculogenic mimicry), increased recruitment of bone marrow-derived cells (e.g., myeloid-derived suppressive cells, tumor-associated macrophages, and tumor-associated neutrophils), and changes in the biological functions and features of local stromal cells (e.g., pericytes, cancer-associated fibroblasts, and endothelial cells). We also review potential biomarkers to predict the response to antiangiogenic therapy in cancer patients, which mainly consist of imaging biomarkers, cellular and extracellular proteins, a certain type of bone marrow-derived cells, local stromal cell content (e.g., pericyte coverage) as well as serum or plasma biomarkers (e.g., non-coding RNAs). Finally, we highlight the recent advances in combination strategies with the aim of enhancing the response to antiangiogenic therapy in cancer patients and mouse models. This review introduces a comprehensive understanding of the mechanisms and biomarkers associated with the evasion of antiangiogenic therapy in cancer, providing an outlook for developing more effective approaches to promote the therapeutic efficacy of antiangiogenic therapy.